Cocooning urban life: Exposure to diversity in neighbourhoods, workplaces and transport. (November 2016) - Boterman, Willem R.; Musterd, Sako
Abstract: Although one's neighbourhood is continuously structuring everyday lives and influences encounters between different people, place of residence is only partially the site where interactions and possibly integration between population categories occur. Another well-known domain is the place of work, where many spend hours per day and may meet various 'others'. However, people's mobility is also strongly differentiated between class and ethnicity. Here too, different modes of transport may offer opportunities for encounter and engaging with others. In order to assess exposure to diversity of individuals from various ethnic and social class backgrounds to 'the other' we focus on these three important realms of daily life: neighbourhoods, workplaces and modes of transport. We use individual level data from the Mobilities Netherlands Database combined with detailed individual level register data from the Social Statistical Database. We found that, overall, higher income natives are, compared to the other combinations of country of origin and income category most frequently cocooning in homogeneous residential, workplace, and mobility spaces. However, native-Dutch with a low income stand out in the residential domain, where they are living more frequently in homogeneous neighbourhoods than high-income natives.